Dora the Explorer. Dora saves the mermaids - Herles, Kathleen, 1991-; Chad, Harrison; Gifford, Chris; Walsh, Valerie; Weiner, Eric.; Nelvana (Firm); Paramount Home Entertainment (Firm) (Hollywood, Calif. : Paramount Home Entertainment, 2007)
Dora and Boots take preschoolers on an exciting underwater adventure to help save the mermaid's kingdom. Dora travels to the bottom of the ocean and finds a hidden treasure chest on Treasure Island.
Dora saves the mermaids -- Fish out of water -- Treasure island.
Title from container.
Based on the characters created by Chris Gifford, Valerie Walsh and Eric Weiner.
"Nick Jr."
Special features: "Clean up song" music video.
Voices: Kathleen Herles, Harrison Chad.
Not rated.
Keywords: Dora the Explorer (Fictitious character) -- Juvenile films; Mermaids -- Juvenile films; Treasure troves -- Juvenile films; Friendship -- Juvenile films; Dora the Explorer (Fictitious character) -- Drama; Mermaids -- Drama; Buried treasure -- Drama; Friendship -- Drama; Television programs; Television programs for children; Films for the hearing impaired; Action and adventure television programs; Adventure -- Animation -- Television series; Fantasy -- Animation -- Television series; Children's -- Animation -- Television series; Television serials; Animated television programs; Fantasy television programs